Los fondos de capital privado como una propuesta innovadora para la financiación del sector agropecuario. Caso: Estructuración para el cultivo de aguacate hass (2014)
The research presented here proposes the adoption of private capital funds as an innovative alternative for financing large projects in the farming sector, focusing on late yield crops due to the fact that these crops require significant investments and do not generate cash flow during the first years to cover the financing charges under traditional financing practices. As a particular case, a proposal for Hass avocado financing with a private capital fund in Colombia is analyzed, taking into account the specific conditions for its production in appropriate regions and taking advantage of the incentives and fiscal benefits that can be obtained.